Quantitative assessment of ulcer wound volume - Rani, A.M.A. (CRC Press, 2014)
Ulcer refers to a discontinuity of the skin exhibiting complete loss of the epidermis that is not short lived. The duration of the ulcer could last from a few weeks to even a few years. Patients suffering from such chronic skin ulcers face a huge loss of quality of life. The patients not only have to endure pain, but also time-consuming outpatient treatment and costs. Leg ulcers are very common, and based on the statistics, 3.5 of all adults in the United States suffer from venous leg ulcers 1. Chronic ulcerative skin lesions affect about 1.5% of the European population and represent an important medical and social problem 2. Â© 2014 by Taylor & Francis Group, LLC.